Adsorption/desorption of ions in liquid crystal nanocolloids: the applicability of the Langmuir isotherm, impact of high electric fields and effects of the nanoparticle's size. Issue 6 (2nd May 2016) - Garbovskiy, Yuriy
ABSTRACT: In this paper, the applicability and limitations of the Langmuir formalism applied to describe the ion adsorption/ion desorption in liquid crystal nanocolloids are discussed. The overall electrical neutrality of liquid crystals and nanoparticles is a key factor enabling the validity of the Langmuir isotherms. The approximation of the Langmuir adsorption isotherm is valid as long as the electrical potential of the nanoparticle's surface is relatively small ( ), and the applied electric field is not very high ( ). Within these limits the Langmuir formalism can describe a broad variety of existing experimental data including the dependence of the concentration of mobile ions in liquid crystal nanocolloids on the size of nano-dopants. Graphical Abstract: